Hubungan Kejadian Diare Dengan Pemberian Susu Formula Pada Bayi Umur 0-1 Tahun Di Wilayah Kerja Puskesmas Banjarbaru Tahun 2013 - Firyal Yasmin; Agus Rahmadi; Noni Setia Rini; STIKES Husada Borneo; Alumni STIKES Husada Borneo (HB PRESS, 2014)
Diarrhea disease remains a major cause of health problems for Indonesian people, both in terms of morbidity and mortality rate. This disease can affect all age groups with morbidity rates ranging from 280 per 1000 population and for children under five suffer from one to one and a half times the episodes of diarrhea each year. Incidence of diarrhea is still a major cause of infant mortality as in the previous period. The aim of this study is correlation of the incidence of diarrhea with formula feeding for 0-1 years old infants in Banjarbaru working area 2013. This research uses the analytical method with cross sectional design. This research was conducted on 42 respondents. Based on the results of the statistical test using the chi-square indicates that there is a correlation of diarrhea case with the consumption of milk formula for infant 0-1 years old in the working wrea of Banjarbaru Public Health Centre Catchment Area 2013.